PENGEMBANGAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA IPA SMP KELAS VII - Nuha, Ulin; Sari, Novilia Mita; Utomo, Anjar Putro; Wahyuni, Sri (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2021)
This study aims to improve science process skills by developing instructional videos of science material for class VII SMP, namely the interaction of living things with their environment. The method of this study is Research and Development (R&D) using ADDIE instructional design. The validation result shows that the developed instructional video classified in the category very good and does not need to be revised with the score of each validator, namely: (1) 87.5%; (2) 92.5%; and (3) 97.5%). The results of the effectiveness of the video based on student questionnaire data showed that: (1) 25.6% of students are strongly agreed; (2) 59,4% of students are agreed; and (3) 15% of students are disagreed. The results of the N-Gain analysis show that the process skills of students after using the instructional videos are in the high (28.1%), medium (59.4%), and low (12.5%) categories. Overall, students’ science process skills increased by 79%. This study concludes that the developed instructional videos can be said to be valid, effective, and improve students’ science process skills. Keywords: Development, Instructional Videos, Science Process Skills